Perancangan Dashboard Sistem Informasi Dengan Metode Scrum Menggunakan Azure Board - Aria Bimantara; Jaka Sutresna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The main problem of project implementation is the difficulty of managing information conveyed to several teams. Both in terms of managing the duration of project work and resources. Scrum is a derivative method of Agile Software Development that is used to run and manage a software development project. The scrum method can organize a team and must have strong communication between team members. Before starting a sprint, each team must have a short meeting for planning and end with a review. Using the scrum method is expected to shorten the program work time because each team has its own tasks. The results obtained can overcome changing requirements during the system development phase, which produces products in accordance with user desires because they get repeated reviews (iterative).